Programa alfabetização na idade certa no estado do Ceará segundo a avaliação Spaece alfa - Freire, Gabriela Moriconi (2015)
The present study promotes an analysis of the relationship between municipal determinants and its direct relation to the degree of development of children's literacy according to the Literacy Program at the Right Age (PAIC), that has as goals, the literacy of all children by the end of 2nd year of elementary school. The data used were taken from the Brazilian Institute of Geography and Statistics (IBGE), the Secretary of Education of the State of Ceará (SEDUCCE), Institute of Economic Research and Strategy of Ceará (IPECE), the National Institute of Educational Studies and Research Anísio Teixeira (INEP), and others, to the 184 Ceará´s municipalities, between the years of 2007-2011. There are few economic studies about literacy considering the PAIC program and the SPAECE-Alpha test.